A group is more than the average of its parts: Why existing stereotypes are applied more to the same individuals when viewed in groups than when viewed alone. (August 2019) - Cooley, Erin; Payne, B. Keith
Categorizing people into groups is fundamental to stereotype formation. Thus, across four studies, we hypothesize that perceiving people in the context of groups (vs. alone) will amplify the application of existing stereotypes. Consistent with hypotheses, our first two studies demonstrate that Black people in groups (vs. the same Black people viewed alone) are perceived as more representative of Black people in general (Study 1), and more representative of negative stereotypes of Black people (Study 2). Similarly, Study 3 finds that positive stereotypes of Asian people (i.e., "hard-working" and "good at math") are perceived as more representative of Asian people in groups than those same Asian people viewed alone. Finally, Study 4 demonstrates that increased stereotyping of groups is driven by attributes associated with groups (i.e., proximity) rather than the number of exemplars. We conclude that groups are not only integral to the formation of stereotypes, but also to their application.